Effect of Crude Plant Extracts on Mushroom Mite, Luciaphorus sp. (Acari: Pygmephoridae) - Prapassorn Bussaman; Chirayu Sa-uth; Paweena Rattanasena; Angsumarn Chandrapatya (Psyche: A Journal of Entomology)
The use of plant extracts for controlling agricultural pests has become increasingly popular in the recent years. Mushroom mite, Luciaphorus sp., is a destructive pest of several mushroom species and has been reported to cause severe loss of mushroom cultivation in many settings. The efficacies of 23 rhizome and leaf extracts were evaluated against female adults of Luciaphorus sp. At 3 days after treatment, the rhizome extracts derived from Curcuma xanthorrhiza Roxb. and Zingiber montanum (Koenig) Link ex Dietr. were found to have very strong acaricidal activities, resulting in 100% mite mortality, followed by Curcuma longa Linn. (98.89%), Zingiber zerumbet (L.) Smith. (97.78%), Kaempferia parviflora Wall. Ex Baker (88.89%), and Zingiber officinale Roscoe. (84.44%). The leaf extracts of Ocimum sanctum Linn. and Melissa officinalis L. also resulted in 100% mite mortality 3 days after treatment, while the other leaf extracts induced mite mortality only below 70%. The results suggested that rhizome extracts of C. xanthorrhiza and Z. montanum and leaf extracts of O. sanctum and M. officinalis have a great potential for future development as natural acaricides for controlling Luciaphorus sp.